Culture and inflation in Weimar Germany - Widdig, Bernd (Weimar and now, 2001)
For many Germans the hyperinflation of 1914-1923 was one of the most decisive experiences of the 20th century. This study investigates the effects of that inflation on German culture during the Weimar Republic.